Ecologies of risk among African American girls in juvenile detention. (January 2018) - Logan-Greene, Patricia; Kim, B.K. Elizabeth; Quinn, Camille R.; DiClemente, Ralph; Voisin, Dexter
Abstract: African American girls are disproportionately represented in juvenile detention, yet less is known about their distinctive and heterogeneous needs, especially regarding their psychosocial contexts. Latent class analysis determined four subgroups based on the adolescent ecology (neighborhood, family, peers) among detained African American girls ages 13–17 (N = 188). The Shielded class (32%) displayed the lowest levels of risk and highest levels of protective factors. The Typical class (24%) was close to the sample average on all indicators, with elevated histories of family incarceration. The Family Distress class (16%) reported the lowest neighborhood risk but was marked by high family risk levels and abuse history. The Highest Risk class (28%) had elevated risk on most indicators but particularly high neighborhood and peer risk. These classes significantly varied by youth social context and mental health. Findings bolster the need to consider the diverse, multidimensional contextual experiences of detained and at-risk African American girls. Highlights: African American girls in detention have received minimal attention in research. Study findings demonstrate heterogeneity based on peer, neighborhood, and family context. LCA found four groups: Hardy, Typical, Family Distress, and Highest Risk classes. Classes differed significantly on social functioning and mental health indicators. Detained African American girls have specific profiles of high risk needing intervention.